Peralatan Dapur Suku-Suku di Kabupaten Sarmi - Rini Maryone (Universitas Cenderawasih, 2021)
Traditional kitchen aquipment has been around since prehistoric humans began to know farming. Along whit the development of science and technology, the use of traditional kitchen aquipment is increasingly, especially in the tribes in Sarmi Regency. Therefore it is necessary to have an effort to preserve the traditional kithen equipment as one of the nation’s wealth heritage. This paper will discuss some traditional equipment in the two tribes in Sarmi Regency, namely the Manirem and Armati tribes, as well as the functions and cultural values contained in traditional kitchen equipment. This research is a descriptive study through a qualitative approach. Data collection techniques carried out through observation in the community (observation), interviews with several informants, documentation and literature studies. By using this method one can find out the kitchen utensils in the two tribes in Sarmi Regency, as well as find out the function and cultural values contained in traditional kitchen utensils in the two tribes in Sarmi district